Integration of electrical components in metal additively manufactured products - Ahmad, Robin; Bui, Davis (My University, 2019)
Abstract As the development in additive manufacturing (AM) is moving at a fast pace, Saab Group { Defence and Security wants to examine all the aspects of the technological development's impact. Traditionally AM has been used to print complex homogeneous non-functional structures, but as a result of major achievements in recent years the possibility to print functional structures has paved the way. A lot research has been done regarding the integration of electrical elements in polymeric AM, but little has been done in metallic AM. The reason for this is the operating temperatures jeopardising the electrical elements survivability. The combination of the physical and virtual domain in the same framework improves maintenance decision and revolutionises safety. Thus this is a key enabler of the upcoming industry 4.0. The report aims to explore and evaluate di erent intelligent structural-healthmonitoring systems which can be integrated into metallic AM parts. This was initially done by deriving a simpli ed cooling plate which lays the foundation of the further described case study. According to the literature ndings, the most promising AM methods has shown to be ultrasonic additive manufacturing (UAM) and selective laser melting (SLM). Furthermore, piezoelectric sensors, thermocouples and resistance temperature detectors has been evaluated. In total 20 di erent concepts were generated and four of them passed the established screening criteria, among which manufacturing complexity and compatibility with AM where some. The four concepts were then divided into three cooling plates based on their characteristics and a fourth cooling plate was representing the baseline solution (a cooling plate with no sensor). A pause-build procedure was implemented in order to integrate Pt100 temperature sensors into an aluminium alloy with SLM and thus form the proof of concepts. In the end, metal prototyping of the concepts with integrated temperature sensors was accomplished. Although, the prototyping plan had to be revised towards the end with additional post-processing. A CT-scan of one of the printed prototypes was conducted in order to observe appeared defects. Through observations and analyses, learnings and conclusions could be obtained to determine the feasibility and limitations of sensor integration in AM products.
Keywords: Maskinteknik; Innovation och entreprenörskap (nyttiggörande); Produktion; Mechanical Engineering; Innovation & Entrepreneurship; Production